INSTRUCTIONAL DESIGN IN ENGLISH LESSON PLANS - Imroatus Solikhah (Center of Language and Cultural Studies, 2014)
The objectives of this study are to describe how indicators, learning objectives and teaching materials are stated in English lesson plans for Elementary School Students based on the criteria of instructional designs using School-Based Curriculum. Five English lesson plans available online are analyzed in this study using content analysis design. The results show that statements of indicators and learning objectives are not matched with the criteria of good instructional design. In addition, learning objectives do not indicate actual teaching materials and action verbs to indicate measurable teaching-learning outcomes do not match to each other.